2003
DOI: 10.1038/sj.cdd.4401153
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic suppression of apoptosis in salivary acinar cells by IGF1 and EGF

Abstract: Tissue homeostasis requires balancing cell proliferation and programmed cell death. IGF1 significantly suppressed etoposide-induced apoptosis, measured by caspase 3 activation and quantitation of cellular subG 1 DNA content, in rat parotid salivary acinar cells (C5). Transduction of C5 cells with an adenovirus expressing a constitutively activated mutant of Akt-suppressed etoposide-induced apoptosis, whereas a kinase-inactive mutant of Akt suppressed the protective effect of IGF1. IGF1 also suppressed apoptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(37 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…1B, lanes 1 and 2), 11.5-fold in sublingual (Fig. 1B, lanes 3 and 4), and 4.9-fold in parotid ( ylation of a substrate peptide (50). In myr-Akt1 female mice, Akt kinase activity increased 1.56-fold in the submandibular gland, 1.78-fold in the sublingual gland, and 1.33-fold in the parotid gland relative to endogenous Akt (Fig.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…1B, lanes 1 and 2), 11.5-fold in sublingual (Fig. 1B, lanes 3 and 4), and 4.9-fold in parotid ( ylation of a substrate peptide (50). In myr-Akt1 female mice, Akt kinase activity increased 1.56-fold in the submandibular gland, 1.78-fold in the sublingual gland, and 1.33-fold in the parotid gland relative to endogenous Akt (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…In some cases, membranes were then stripped, as previously described (35), reblocked in Tris-buffered saline (10 mM Tris [pH 7.4], 150 mM NaCl, and 0.05% Tween 20) with 5% nonfat dry milk (Carnation), and probed with a second antibody. The activation of Akt kinase activity was quantitated with a radioactive Akt kinase assay kit (Upstate Biotechnology, Lake Placid, NY) using 300 g of tissue lysates according to the manufacturer's instructions (50).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[33][34][35][36][37] Musaro and colleagues 37,38 demonstrated that overexpression of locally acting IGF-1 (mIGF-1) improves muscle function in mouse models of senescence, injury, myodystrophy, or amyotrophic lateral sclerosis. In muscle and satellite cells, we found that CKD impaired IGF-1R-mediated signaling (Supplemental Figure 2, A and B), and when we suppressed the IGF-1 receptor in mice (IGF-1R-KO), satellite cell activation and muscle regeneration were reduced as in CKD mice (Figure 4).…”
Section: Basic Research Wwwjasnorgmentioning
confidence: 99%